ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI DISIPLIN PEGAWAI NEGERI SIPIL KELURAHAN DI LINGKUNGAN PROVINSI DKI JAKARTA - Noviyani Rizqiyah; Lina Miftahul Jannah (SWATANTRA, 2017)
Discipline is an important factor to have by all civil servants, especially civil servants in administrative villages (kelurahan) in DKI Jakarta Province in order to provide service to the public. In reality, the problem of discipline still exists sourcing from both the civil servants or the public behaviour. Based on that, this research was conducted to explain what factors affect the discipline of civil servants in administrative villages in DKI Jakarta Province. The theory used in this research is theory of employee discipline. The research used quantitative methods with questionnaire as research instrument and analysed using Rho Spearman Test. Sampling was done using simple random sampling. Research results show that from the seven factors  that  influence employee discipline, the strongest correlation coefficient was on the variable leader’s courage to take action and followed by the variable certain rules to serve as a guide by employees.Keywords: discipline, civil servants service